Modulation of ACE2 Glycosylation as a Therapeutic Target for SARS-CoV-2 Infection in Chinese Populations - Fangyin Chou; Wei Tang (Sriwijaya Journal of Internal Medicine, 2024)
Introduction: The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has presented a significant global health challenge. The virus utilizes the angiotensin-converting enzyme 2 (ACE2) receptor for host cell entry, a process mediated by the viral spike protein. Glycosylation of ACE2 plays a crucial role in this interaction. This study investigates the potential of modulating ACE2 glycosylation as a therapeutic strategy for SARS-CoV-2 infection, specifically focusing on Chinese populations. Methods: A multi-faceted approach was employed. Bioinformatic analysis of ACE2 glycosylation patterns in Chinese populations was conducted using publicly available genomic data. In vitro experiments were performed using human cell lines expressing different ACE2 glycoforms to assess the impact of glycosylation on viral binding and entry. Clinical data from a cohort of Chinese COVID-19 patients were analyzed to correlate ACE2 glycosylation profiles with disease severity and outcomes. Results: Bioinformatic analysis revealed distinct ACE2 glycosylation patterns in the Chinese population compared to other global populations. In vitro experiments demonstrated that specific ACE2 glycoforms significantly influenced SARS-CoV-2 spike protein binding and viral entry efficiency. Clinical data analysis showed a correlation between certain ACE2 glycosylation profiles and increased disease severity in COVID-19 patients. Conclusion: Modulation of ACE2 glycosylation represents a promising avenue for developing novel therapeutic strategies against SARS-CoV-2 infection in Chinese populations. Further research is needed to translate these findings into clinical applications, including developing targeted therapies that can alter ACE2 glycosylation to reduce viral entry and disease severity.